Examination of the Reliability of a Robustness Test for the Self-Directed Channel Carbon-Based Memristors by Reading Their DC Resistance - Ceylan Dalmış Ercan; Reşat Mutlu; Ertuğrul Karakulak (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2023)
An ideal memristor that has been theoretically predicted almost a half-century ago is a nonlinear power dissipating circuit element. Nowadays, memristive systems such as thin films which are not ideal memristors are also called memristors. Such systems have current-dependent behavior and nonlinear charge-dependent electrical resistance. Self-directed channel Carbon-, Tungsten-, Chrome-, and Tin-based memristors have become commercially available nowadays and they are used for research purposes. All circuit components must be tested before their usage. It is expected that memristors will become commonly used in electronic circuits in the future. However, the literature has just a few memristor tests reported. To the best of our knowledge, there is not a suggested robustness test for the self-directed channel Carbon-based memristors in the literature. In this study, A recently suggested memristor robustness test which could be made using just a multimeter is modified using a series resistor. The test is tried on the Self-Directed Channel Carbon-Based memristors. Unfortunately, the test is found unreliable and invalid for the self-Directed Channel Carbon-Based memristors.